Penerapan Komunikasi Persuasif pada Program Laku Pandai untuk Meningkatkan Inklusi Keuangan di Era Teknologi Digital (Artificial Intellegence) - Yoseph Hari Pramono; Ummanah Ummanah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine how the process of implementing persuasive communication carried out by Laku Pandai program agents influences and increases financial inclusion in the community. The research method used is a qualitative approach with a case study type. This approach was chosen to gain an understanding of the communication strategies implemented by Laku Pandai agents and how artificial intelligence technology is utilized to support these communication activities. Data were collected through interviews, direct observation, and relevant documentation, which were then analyzed descriptively-qualitatively. The results of the study indicate that the application of persuasive communication based on artificial intelligence by Laku Pandai program agents is able to increase the effectiveness of information delivery and build public trust in financial services. It can be concluded that this technology supports agents in delivering more personal, relevant, and data-based messages, thus contributing positively to increasing financial inclusion in the community. Keywords: Artificial Intelligence, Financial Inclusion, Persuasive Communication.